2015
DOI: 10.1186/s13000-015-0447-1
|View full text |Cite
|
Sign up to set email alerts
|

MDR-1 and MRP-1 activity in peripheral blood leukocytes of rheumatoid arthritis patients

Abstract: BackgroundRheumatoid Arthritis is a chronic disease leading to decreased quality of life with a rather variable response rate to Disease Modifying Anti Rheumatic Drugs. Methotrexate (MTX) is the gold standard therapy in Rheumatoid Arthritis. The Multidrug resistance Related Protein and Multi Drug Resistance protein 1, also called P-glycoprotein-170 transporters can alter the intracellular concentration of different drugs. Methotrexate is an MRP1 substrate and thus the functional activity of MRP1 might have a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Performing real‐time transporter activity measurements using fluorescent reporter substrates is highly beneficial in the clinical setting for personalized therapy and monitoring in certain hematologic malignancies and in autoimmune diseases, since the activities of MDR1, MRP1, and BCRP serve as biomarkers to predict the patient's response to small molecule therapy in treatment naïve conditions and during small molecule drug treatment . Furthermore, the determination of transporter activity is also relevant in cell lines in pharmaceutical research.…”
Section: Introductionmentioning
confidence: 99%
“…Performing real‐time transporter activity measurements using fluorescent reporter substrates is highly beneficial in the clinical setting for personalized therapy and monitoring in certain hematologic malignancies and in autoimmune diseases, since the activities of MDR1, MRP1, and BCRP serve as biomarkers to predict the patient's response to small molecule therapy in treatment naïve conditions and during small molecule drug treatment . Furthermore, the determination of transporter activity is also relevant in cell lines in pharmaceutical research.…”
Section: Introductionmentioning
confidence: 99%
“…In early RA, leukocytes invade the synovial joints followed by other pro-inflammatory mediators which instigate an inflammatory cascade and provoke synovitis (Smolen et al, 2018). Activated monocytes and T cells, both a source of proinflammatory cytokines such as TNF-a, can be found in peripheral blood (Batliwalla et al, 2005) and many RA studies have used peripheral blood cells to identify disease-related genes (Edwards et al, 2007;Micsik et al, 2015;Kuuliala et al, 2017;Li et al, 2020). The common therapy for the disease includes the use of Disease-modifying anti-rheumatic drugs (DMARDs).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study found decreased functional activity of both MDR1 and MRP1 in peripheral blood leukocytes of RA patients compared to non-RA and healthy controls. 26 Another study found downregulation of MDR1 expression in during early stages of methotrexate treatment in patients with RA. 27 Part of this incongruence between MDR function and grade of inflammation could also be ascribed to the various endogenous functions of these transporters that include transport of several metabolites and signaling molecules, besides inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%